PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN OBYEK WISATA WATERFRONT DI KOTA PONTIANAK - Nur, Dini Giatri; Ulfah, Maria; Harjanti, Diah Trismi (Universitas Tanjungpura, 2024)
Pontianak City has the longest river in Indonesia, the Kapuas River with a length of 1,143 KM. The Kapuas River plays an important role for the surrounding community because it has strategic value and function. So that the Kapuas River in Pontianak City is the target of revitalization of waterfront development. This study aims to determine community participation in the development of waterfront tourism objects in Pontianak City. The research method used is descriptive with a qualitative research form. The data source for this study is the Head of the Village and RT / RW Benua Melayu Laut and the data is the result of observation, documentation and interviews with the Head of the Village and RT / RW Benua Melayu Laut. The results of this study indicate that there is community participation in the development of waterfront tourism objects in Pontianak City which includes participation of ideas, participation of labor, participation of property, participation of skills / abilities, social participation and factors influenced by supporting factors, namely willingness, ability, and opportunity, as well as inhibiting factors, namely dependency